A contemporary definition of periprocedural myocardial injury after percutaneous coronary intervention of chronic total occlusions. (25th November 2020) - Winter, M.P; Goliasch, G; Ayoub, M; Bartko, P; Mashayekhi, K; Ferenc, M; Buettner, H; Hengstenberg, C; Neumann, F.J; Toma, A
Abstract: Background: Coronary chronic total occlusion (CTO) recanalization represents the most technically challenging percutaneous coronary interventions (PCI). The complexity harbours a significant increased risk risk for complications with CTO PCI as compared to non-CTO PCI. However there are evidenced biomarker cut-off levels that help to identify those patients at risk for an unfavorable clinical outcome. Objective: This study aimed to assess the prognostic impact of postprocedural troponin T increase and mortality in patients undergoing CTO-PCI in order to define the threshold, where procedural related myocardial injury drives mortality. Methods: We enrolled a total of 3712 consecutive patients undergoing PCI for at least one CTO lesion and performed comprehensive troponin Tmeasurements 6, 8, and 24 hours after the procedure. All-cause mortality was defined as the primary study endpoint. Results: Using spline curve analysis, we observed that a more than 18-fold increase of troponin above the upper reference limit (URL) is significantly associated with mortality. In the Cox regression analysis we observed a crude hazard ratio (HR) of 2.32 (95% CI 1.83–2.93, P<0.001) for a ≥18fold increase compared to patients with post-procedural troponin increase <18-fold of the URL.Results remained virtually unchanged after bootstrap- or clinical confounder-based adjustment. Conclusion: This large-scale outcome study demonstrates for the first time the prognostic value of post-procedural troponin T elevation after PCI in CTO patients. We could define a threshold for procedure related myocardial injury in CTO patients that differ non- CTO patients and may help guide the postprocedural clinical care in this high risk patient population. Funding Acknowledgement: Type of funding source: None